Fabricating a new Rheometer for Concrete (Journal of Engineering, 2014)
A new concrete rheometer is introduced including its innovation, actual design, working rules,calibration, and reliability. A modified design of Tattersall two-point device is created. Some ofcomponents are purchased from local and foreign markets, while other components and themanufacturing process are locally fabricated. The matching viscosity method of determining the mixerviscometer constants is demonstrated and followed to relate torque and rotational speed to yield stressand viscosity (Bingham parameters). The calibration procedures and its calculation are explained.Water is used as a Newtonian fluid, while; cement paste (cement + water) with w/c ratio equal to(0.442) is used as a non-Newtonian fluid. The cement paste is tested in “Petroleum Research andDevelopment Center” by “OFITE Model 800 Viscometer”. In order to verify the reliability of the newrheometer, an Artificial Neural Network (ANN) model with a well selected bank of data is constructed;and (16) Mixes of Self Compacting Concrete (SCC) are constructed, mixed and tested by the newRheometer. The results from model (predicted) and those from the experimental work (measured) werefound to have very good degrees of correlation and matching, which indicates that the new rheometercan be reliable.